2021
DOI: 10.3390/molecules26051409
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Main Protease Active Site Ligands in the Human Metabolome

Abstract: In late 2019, a global pandemic occurred. The causative agent was identified as a member of the Coronaviridae family, called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In this study, we present an analysis on the substances identified in the human metabolome capable of binding the active site of the SARS-CoV-2 main protease (Mpro). The substances present in the human metabolome have both endogenous and exogenous origins. The aim of this research was to find molecules whose biochemical and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 64 publications
(78 reference statements)
0
19
1
Order By: Relevance
“…Rutin (a polyphenolic flavonoid) may able a potential inhibitor as it is able to form several hydrogen bonds and σ - π stacking interactions with various amino acids of Mpro in anchoring and blocking the substrate into the active pocket of the catalytic center [ 157 ]. In vivo and in silico studies have demonstrated that silymarin and its derivative silybin (a flavonoid from the group of flavonolignans) are able to inhibit SARS-CoV-2 main protease [ 158 ]. Another authors found luteolin to be effective in blocking the S2 protein of SARS-CoV [ 159 ].…”
Section: The Possible Therapeutic Approach Related To Oxidative Stres...mentioning
confidence: 99%
“…Rutin (a polyphenolic flavonoid) may able a potential inhibitor as it is able to form several hydrogen bonds and σ - π stacking interactions with various amino acids of Mpro in anchoring and blocking the substrate into the active pocket of the catalytic center [ 157 ]. In vivo and in silico studies have demonstrated that silymarin and its derivative silybin (a flavonoid from the group of flavonolignans) are able to inhibit SARS-CoV-2 main protease [ 158 ]. Another authors found luteolin to be effective in blocking the S2 protein of SARS-CoV [ 159 ].…”
Section: The Possible Therapeutic Approach Related To Oxidative Stres...mentioning
confidence: 99%
“…It is very interesting to note that for Chelidonium majus L., the only herbal source of Chelidimerine, significant in vitro inhibitory activity against cysteine proteinases has already been reported (133). In addition, some Physalin derivatives have very recently been introduced as potent M pro inhibitors (78,134,135) and Hinokiflavone which belongs to biflavonoid compounds, has already been identified as the antiviral potential of H1N1 influenza inhibitor (55). Even more interesting is the fact that, 5 out of 13 phytochemicals -two flavonoid glycosides (6 and 7 in Figure 2), two biflavonoid compounds (8 and 13), and Pongamoside A (11)contain the flavonoid scaffold which is well-known for its striking antiviral potential against diverse coronaviruses (9,55,60,63,(66)(67)(68)(69)71,76,(82)(83)(84)87).…”
Section: Resultsmentioning
confidence: 99%
“…3CLpro (also known as Mpro) is the major betacoronavirus protease necessary for viral RNA translation in polyprotein synthesis [ 10 , 30 ]. Recently, the x-ray structures and α-ketoamide complex of SARS-CoV-2 3CLpro have been reported [ 10 , 30 , 61 ].…”
Section: Therapeutic Approaches To Sar-cov-2 Infectionmentioning
confidence: 99%
“…3CLpro (also known as Mpro) is the major betacoronavirus protease necessary for viral RNA translation in polyprotein synthesis [ 10 , 30 ]. Recently, the x-ray structures and α-ketoamide complex of SARS-CoV-2 3CLpro have been reported [ 10 , 30 , 61 ]. Two compound pulmonary tropism pyridine-containing α-ketoamides, called 13a and 13b, exerted pharmacokinetic properties at sufficient concentration in the lungs and bronchial-alveolar liquid lavage of mice within 4 to 24 h of administration [ 47 ].…”
Section: Therapeutic Approaches To Sar-cov-2 Infectionmentioning
confidence: 99%